FREQUENCY AND MODALITY OF EXERCISE ON PAIN AND INDEPENDENCE IN ELDERLY INDIVIDUALS WITH OSTEOARTHRITIS: A CROSS-SECTIONAL STUDY - Felipe Marrese Bersotti; Reniery Pereira Da Silva; Angelica Castilho Alonso; Guilherme Carlos Brech; Paula Regina Mendes da Silva Serrão; Ulysses Fernandes Ervilha (Acta Ortopédica Brasileira)
Abstract Background: Regular physical exercise promotes pain relief, reducing the central facilitation of pain mechanisms. Objective: Evaluate the effect of different frequencies of physical exercise (once, twice, or three times a week) on different modalities (aerobic training, stretching training, and strength training), on the pain in the knee joint, and on the level of independence on people with knee osteoarthritis. Methods: Is cross-sectional and used the STROBE-Checklist: cross-sectional studies. A total of 193 elderly people were evaluated, pain and functional independence were analyzed. Results: For the pain variable, there was a statistical difference in favor of the intervention in the comparisons control versus strength 1 and 2 times a week and stretching 3 times a week already in the Lawton variable, only the comparison control versus aerobic 1 time a week did not prove to be statistically dignified. Conclusion: The exercise modality and the weekly frequency seem to affect the perception of pain, stretching exercises performed three times a week, as well as muscle strengthening exercises, regardless of weekly frequency are efficient in joint pain analgesia. Practicing muscle strength exercises, regardless of weekly frequency and aerobic and stretching exercises at least twice a week, increases and/or maintains IADL. Level of Evidence II; Cross-sectional Study.